Discrimination against pregnant women at the workplace / Zaileen Nadia Zubir and Nurul Izzah Hasan Basri - Zubir, Zaileen Nadia; Hasan Basri, Nurul Izzah (2007)
This research is conducted for the purpose of reviewing the current law on the legal protection for women from any discrimination at workplace in Malaysia and international. Besides that, it is conducted to provide a better understanding and awareness regarding the legal protection for women against discrimination in Malaysia in comparison with the UK, Canada and Australia laws. This research would be conducted through library research that includes primary and secondary sources. The importance of the study is to provide useful legal data and information.